Using of Buserelin to Induce Ovulation in the Purebred Arabian Mares (Journal of Hama University, 2019)
Twenty Mares, 5-10 years old, are used in this present study to evaluate the administration of the GnRH analogue Buserelin to induce ovulation to determine the preferred time of mating and increasing fertility rate in the Purebred Arabian Mares during the breeding season.Mares were divided randomly into two groups (10 mares per group). In the experimental group (G1) Buserelin (40 µg) is injected twice at 12 hours interval. The first dose of Buserelin (20 µg) is injected when the dominant follicle reach a diameter of (45±3mm). In the control group (G2), 5 ml physiological solution is injected twice at 12 hours interval at the same time of administration of Buserelin in the experimental group. The mares are then examined every 6 hours to determine the ovulation time. Mares are mated only once after 24 hours of the first dose of Buserelin. The Pregnancy was then examined by ultrasound in 18, 30 and 90 days.Results show a significant difference (P